An Examination of Meaningful Experiences During Sport Education - Alshuraymi, Ali Nasser; Hastie, Peter (CV Rezki Media, 2024)
Background: In recent research years, there has been an increasing focus on the meaningfulness of physical education experiences. While it has been suggested that certain curriculum models such as sport education or cooperative learning provide opportunities for meaningful engagement in physical education, to date there has been no empirical study of those claims. Objectives: The purpose of this study was to quantitatively examine students’ perceptions of meaningfulness in two physical education contexts: traditional multi-activity format, and sport education. Methods: Sixty seventh-grade students aged 12 to 14 completed a 20-item survey titled